2006
DOI: 10.1080/02841860600904854
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study on stereotactic body radiotherapy of colorectal metastases

Abstract: (2006) Phase II study on stereotactic body radiotherapy of colorectal metastases, Acta Oncologica, 45:7,[823][824][825][826][827][828][829][830]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
230
2
16

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(254 citation statements)
references
References 31 publications
6
230
2
16
Order By: Relevance
“…While SBRT for liver metastases and primary tumors is a relatively new concept, a large body of retrospective literature is available describing early treatment results (Hoyer et al, 2006;Mendez Romero et al, 2006;Wulf et al, 2006;Lee et al, 2009;Rusthoven et al, 2009;van der Pool et al, 2010;Chang et al, 2011;Vautravers-Dewas et al, 2011) including four prospective Phase I studies (Schefter et al, 2005;Lee et al, 2009;Goodman et al, 2010;Rule et al, 2011). The earliest phase I trial reported by Schefter et al (2005) established the benefit and safety of SBRT for liver metastases with eligible patients having 1-3 lesions, tumor diameters <6 cm, and adequate liver function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While SBRT for liver metastases and primary tumors is a relatively new concept, a large body of retrospective literature is available describing early treatment results (Hoyer et al, 2006;Mendez Romero et al, 2006;Wulf et al, 2006;Lee et al, 2009;Rusthoven et al, 2009;van der Pool et al, 2010;Chang et al, 2011;Vautravers-Dewas et al, 2011) including four prospective Phase I studies (Schefter et al, 2005;Lee et al, 2009;Goodman et al, 2010;Rule et al, 2011). The earliest phase I trial reported by Schefter et al (2005) established the benefit and safety of SBRT for liver metastases with eligible patients having 1-3 lesions, tumor diameters <6 cm, and adequate liver function.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic body radiation therapy (SBRT) is used to deliver ablative doses of radiation to an extracranial target with high precision and rapid fall-off that spares surrounding tissues. Early SBRT results revealed excellent tolerance and local control rates for liver metastases and primary liver tumors (Hoyer et al, 2006;Mendez Romero et al, 2006;Wulf et al, 2006;Lee et al, 2009;Rusthoven et al, 2009). The CyberKnife system (Accuray Inc., Sunnyvale, CA, USA) has several features that make it well suited for liver SBRT.…”
Section: Introductionmentioning
confidence: 99%
“…Hoyer et al [83] described a phase II trial of SBRT for predominantly hepatic, unresectable CRC metastases and reported 2-year local or distant progression-free survival rates of 19% with overall survival of 38%. The prescribed dose was 45 Gy to the isocenter in three fractions.…”
Section: Recent Experience With Sbrt For Secondary Liver Tumorsmentioning
confidence: 99%
“…Hoyer et al 12 describes other prognostic factors related to improved local control including smaller tumor volumes, potentially non-CRC metastases, metachronous liver metastases and absence of previous chemotherapy. …”
Section: Other Prognostic Factorsmentioning
confidence: 99%
“…10,11 Dose to the target is most often defined on the prescription isodose surrounding the PTV, which varies from 65 to 90%, and sometime on the isocenter. 7,12 Using intensity modulated radiation therapy (IMRT), the dose is prescribed to the mean dose in the PTV, and is less heterogeneous. 6 From a radiobiological point of view, the question of whether a classic radiobiological modeling, with the linearquadratic (LQ) model, is appropriate for large doses per fraction remains debated.…”
Section: Dose Prescription and Treatment Issuesmentioning
confidence: 99%